2017
DOI: 10.1007/s40265-017-0689-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Drugs in Multiple Myeloma: Mechanisms of Action and Clinical Experience

Abstract: Over the last two decades, the outcomes for patients with multiple myeloma, a plasma cell malignancy, have dramatically improved. The development of the immunomodulatory drugs (IMiDs) which include thalidomide, lenalidomide, and pomalidomide, has contributed significantly to these improved outcomes. While thalidomide is now less commonly prescribed, lenalidomide is widely used in the treatment of newly diagnosed transplant-eligible and transplant-ineligible patients, in the maintenance setting post-transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
184
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(187 citation statements)
references
References 196 publications
(189 reference statements)
0
184
0
3
Order By: Relevance
“…The immunomodulatory drugs (IMiDs), thalidomide, lenalidomide and pomalidomide have also made a major impact in the management of MM. The anti‐MM effects of IMiDs are related to their binding to the E3 ubiquitin ligase cereblon (CRBN) and subsequent ubiquitination and degradation of two B‐cell transcription factors, Ikaros (IKZF1) and Aiolos (IKZF3) (Holstein & McCarthy, ). A landmark study identified CRBN as a primary target in thalidomide teratogenicity, further demonstrating that thalidomide binds to CRBN, disrupting the function of the E3 ubiquitin ligase complex, ultimately leading to the downregulation of fibroblast growth factor genes and the teratogenetic affects associated with thalidomide (Ito et al , ).…”
Section: Immunomodulatory Agents Used To Treat Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…The immunomodulatory drugs (IMiDs), thalidomide, lenalidomide and pomalidomide have also made a major impact in the management of MM. The anti‐MM effects of IMiDs are related to their binding to the E3 ubiquitin ligase cereblon (CRBN) and subsequent ubiquitination and degradation of two B‐cell transcription factors, Ikaros (IKZF1) and Aiolos (IKZF3) (Holstein & McCarthy, ). A landmark study identified CRBN as a primary target in thalidomide teratogenicity, further demonstrating that thalidomide binds to CRBN, disrupting the function of the E3 ubiquitin ligase complex, ultimately leading to the downregulation of fibroblast growth factor genes and the teratogenetic affects associated with thalidomide (Ito et al , ).…”
Section: Immunomodulatory Agents Used To Treat Myelomamentioning
confidence: 99%
“…Finally, pomalidomide is a third generation IMiD approved for relapsed/refractory MM patients, exhibiting efficacy in those who have previously been treated with bortezomib and lenalidomide. (Holstein & McCarthy, ). Table details important phase III studies.…”
Section: Immunomodulatory Agents Used To Treat Myelomamentioning
confidence: 99%
“…PIs act through multiple mechanisms to suppress tumor survival pathways and to arrest tumor growth, tumor spread and angiogenesis [14]. IMiDs increase T-cell and natural killer (NK) cell activation, induce apoptosis and inhibit cell adhesion molecules [15].…”
mentioning
confidence: 99%
“…Another issue of clinical relevancy concerns CRBN, the ClC-1-binding substrate receptor protein of the CUL4 E3 ligase complex. CRBN is known to be the binding target of thalidomide and lenalidomide (194)(195)(196), both immunomodulatory drugs used for the treatment of multiple myeloma (197,198). Common side effects of thalidomide and lenalidomide treatments include muscle weakness and muscle cramps (197,199), suggesting the presence of drug-induced hyperexcitability in skeletal muscles.…”
Section: Clinical Significancementioning
confidence: 99%